Impact of physical and nutritional enrichment on Mulard ducks’ performance and meat quality - Eid, Gehad; Khalil , Fatma; Emeash , Hosny H.; Abd El-Halim , Amany; Abdelghany, Asmaa K. (Journal of Advanced Veterinary Research, 2026)
Poor animal welfare has detrimental impacts on human health and welfare, and damaging effects on the environment. The cultivation of ducks contributes considerably to the production of poultry meat worldwide. Environmental enrichment (EE) approaches have been advantageous for alleviating stress, so housing conditions have prominent effects on animal welfare and, in turn, efficiency of production. Therefore, the objective of this study was to assess and compare the impact of the provision of a tunnel as a physical enrichment (PE) or nutritional enrichment (NE) or combination of both physical and nutritional enrichment on animal welfare, productive performance, and meat quality of Mulard ducks. One hundred and eight 14-day-old Mulard ducklings were distributed at random to 4 groups: Control group (C), Tunnel-enriched group (E): tunnel-based physical environmental enrichment, Moringa-enriched group (Mo): feed Moringa Oleifera leaves powder, and Moringa + Tunnel-enriched group (Mo+E). The performance and growth parameters measured, carcass properties, meat quality, and economic efficiency were assessed. The data obtained showed that growth performance, weight gain, carcass properties, and meat quality measures, as well as economic efficiency, were positively influenced by the provision of a combination of PE and NE and\ or NE alone. Despite the increase in total costs associated with the addition of MO leaf powder, there was an improvement in economic efficiency, particularly in the MO+E and Mo groups. Thus, the provision of a combination of physical and nutritional enrichment improves animal welfare and consequently increases production efficiency, as well as satisfies consumer needs.